2023
DOI: 10.3390/ncrna9060064
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model Based on microRNAs for the Diagnosis of Essential Hypertension

Amela Jusic,
Inela Junuzovic,
Ahmed Hujdurovic
et al.

Abstract: Introduction: Hypertension is a major and modifiable risk factor for cardiovascular diseases. Essential, primary, or idiopathic hypertension accounts for 90–95% of all cases. Identifying novel biomarkers specific to essential hypertension may help in understanding pathophysiological pathways and developing personalized treatments. We tested whether the integration of circulating microRNAs (miRNAs) and clinical risk factors via machine learning modeling may provide useful information and novel tools for essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Intriguingly, evidence support the significance of miR-378 and miR-361 in essential hypertension. [31][32][33] Among the miRNAs with expression levels negatively correlated with LVMI, miR-30, miR-10, have previously been correlated with various cardiacrelated pathological conditions. [34][35][36][37] Thus, collectively, our RNA and small RNA seq data provide evidence for differential expression of anti-angiogenic gene VASH1 and its predicted miRNAs.…”
Section: Candidate Vash1 Micrornas As Predictors Of Hypertension and ...mentioning
confidence: 99%
“…Intriguingly, evidence support the significance of miR-378 and miR-361 in essential hypertension. [31][32][33] Among the miRNAs with expression levels negatively correlated with LVMI, miR-30, miR-10, have previously been correlated with various cardiacrelated pathological conditions. [34][35][36][37] Thus, collectively, our RNA and small RNA seq data provide evidence for differential expression of anti-angiogenic gene VASH1 and its predicted miRNAs.…”
Section: Candidate Vash1 Micrornas As Predictors Of Hypertension and ...mentioning
confidence: 99%
“…miRNAs play a signi cant role in regulating key genes and have important biological functions in vascular remodeling and organ damage, particularly in the heart and kidneys ). It has been reported that miRNAs can serve as novel biomarkers for the pathogenesis of EH and become new targets for the prevention and diagnosis of EH (Jusic et al 2023). The miR-125a-5p/miR-125b-5p pathway enhances the pathological activation of angiotensin II-AT1R in mouse distal convoluted tubule cells by inhibiting Atrap.…”
Section: Introductionmentioning
confidence: 99%